Acute effects of commercial group exercise classes on arterial stiffness and cardiovagal modulation in healthy young and middle-aged adults: A crossover randomized trial - Xavier Melo; Adma Lopes; Raquel Coelho; Bruno Simão; Isabel Oliveira; João L. Marôco; Sérgio Laranjo; Bo Fernhall; Helena Santa-Clara (PLoS ONE, 2025)
Background Arterial stiffness and cardiac autonomic function are crucial indicators of cardiovascular health. Acute exercise and age impact these parameters, but research often focuses on specific exercise activities, lacking ecological validity. Methods We examined the acute effects of commercially available group fitness classes (indoor cycling, resistance training, combined exercise) on arterial stiffness and vagal-related heart rate variability (HRV) indices in twelve young and twelve middle-aged adults. Participants attended four sessions, including exercise and control conditions, with measurements taken at rest and during recovery. Results Middle-aged, but not young adults, showed reductions in central and peripheral systolic blood pressure 20-min into recovery across all exercise modalities (range: -7 to -8 mmHg p < 0.05). However, arterial stiffness remained unchanged. Similarly, vagal-related HRV indices (range: -0.51 to -0.90 ms, p < 0.05) and BRS (-4.03, p < 0.05) were reduced immediately after exercise, with differences persisting 30 min into recovery only after indoor cycling. Resistance and combined exercise elicited similar cardiovagal modulation and delayed baroreflex sensitivity recovery to cycling exercise, despite higher energy expenditure during indoor cycling (+87 to +129 kcal, p < 0.05). Conclusion Acute group fitness classes induce age-dependent alterations in blood pressure, but not in arterial stiffness or cardiovagal modulation. While the overall cardiovascular effects were generally consistent, differences in autonomic recovery were observed between exercise modes, with prolonged effects seen after indoor cycling. This suggests that exercise prescription should consider both age and exercise modality, as well as recovery time. The findings also emphasize the importance of ecological validity in exercise interventions, highlighting that acute effects on cardiovascular health in real-world settings may differ from those observed in controlled laboratory environments (ID: NCT06616428).